Workshop Birth Companion untuk Menurunkan Kecemasan Ibu Bersalin - Shinta Nur Rochmayanti; Alief Ayu Purwitasari; Arkha Rosyaria Badrus; Miftahul Khairoh; Kholifatul Ummah (Rena Cipta Mandiri, 2026)
Anxiety before childbirth may reduce maternal comfort and potentially affect the labor process. This community service program aimed to strengthen the husband's role as a birth companion through a childbirth support workshop. The target participants were couples/pregnant women in the partner area. The program consisted of education on stages of labor, training in non-pharmacological support techniques including effleurage massage, counterpressure, labor positioning, breathing exercises, positive affirmation, and distribution of self-learning educational media. Evaluation was conducted through pre-test and post-test knowledge assessment, observation of husbands' practical skills, and maternal anxiety assessment using the Hamilton Anxiety Rating Scale. The results showed an increase in husbands' practical skills from approximately 25-30% before the workshop to an average of 88% after the intervention. Maternal anxiety also decreased, with most respondents shifting from severe anxiety to mild or no anxiety. The workshop indicates that structured husband involvement can enhance physical and psychological support for mothers during childbirth.